Low‐loss reverse blocking IGBT with PNM structure and trench collectors. Issue 6 (1st March 2019) - Liu, Fenghao; Huang, Mingmin; Li, Rui; Lai, Li; Gong, Min
Abstract : A reverse blocking insulated gate bipolar transistor (IGBT) with partially narrow mesa (PNM) structure and trench collectors is proposed. An n‐type carrier stored (n‐cs) layer is introduced between two trench gates with the bulgy bottom, forming the PNM structure, which nicely shields high electric field from the n‐cs layer at the forward blocking state. Hence, a highly doped n‐cs layer can be used to enhance the carrier storage effect in the n‐drift region at on‐state to reduce the on‐state voltage [ V CE(sat) ]. Besides, an n‐buffer layer is introduced between two trench collectors at the back side, acting as a field‐stop (FS) layer at forwarding blocking state. At the reverse blocking state, the trench collectors shield high electric field from the n‐buffer region and the n‐cs layer acts as an FS layer, which ensures a high reverse breakdown voltage. Numerical simulation results show that the 1.4 kV proposed reverse blocking‐IGBT can use a 38% thinner n‐drift region and obtain a 45% lower V CE(sat) than the conventional counterpart.